Learning Chinese characters : a revolutionary new way to learn and remember the 800 most basic Chinese characters : HSK level - Matthews, Alison; Matthews, Laurence (Tuttle Publishing, 2007)
This user-friendly book is aimed at helping students of Mandarin Chinese learn and remember Chinese characters. At last-there is a truly effective and enjoyable way to learn Chinese characters! This book helps students to learn and remember both the meanings and the pronunciations of over 800 characters. This otherwise daunting task is made easier by the use of techniques based on the psychology of leaning and memory. key principles include the use of visual imagery, the visualization of short ""stories, "" and the systematic building up of more complicated characters from basic building bloc.